2018
DOI: 10.15406/mojor.2018.10.00446
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation signal correlation and “Swiss spinal questionnaire” in lumbar stenosis

Abstract: Introduction:The spinal stenosis is the most common disease of the lumbar spine over 65 years. More specific symptoms are the progressive neurogenic claudicating, pain and muscle strength deficit started to walk. A form of clinical evaluation is performed by the "Swiss Spinal Stenosis Questionnaire" (SSSQ). An objective assessment can be made with sedimentation signal analysis seen by magnetic resonance imaging (MRI). The objective of this study is to correlate the clinical analysis through the SSSQ and sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…1 Age was not significant in the intensity of symptoms. Barz et al 3 found that 94% of the patients had no sedimentation signal, while our data indicated 69.23%, approaching the data found by Laudato et al 8…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…1 Age was not significant in the intensity of symptoms. Barz et al 3 found that 94% of the patients had no sedimentation signal, while our data indicated 69.23%, approaching the data found by Laudato et al 8…”
Section: Discussionsupporting
confidence: 79%
“…1 The most specific symptoms are progressive neurogenic claudicating accompanied by pain and deficit of muscular strengh initiated when walking. 2 Barz et al 3 demonstrated that patients without vertebral stenosis submitted to magnetic resonance imaging (MRI) presented a migration of the roots to the dorsal region of the dural sac due to gravitational action, whereas in patients with vertebral stenosis they found images of the roots without this conformation, thus defining the first as a sign of sedimentation present and the second as a sign of absent sedimentation ( Figure 1). 4,5 Patients with lumbar stenosis present variable clinical manifestations such as neurogenic claudication that manifests as a sensation of weight in the lower back radiating to the buttocks and lower limbs, numbness, weakness or burning; and sciatica as the most common complaints.…”
Section: Introductionmentioning
confidence: 99%